Edaphic macrofauna in organic cultivation of sugar cane in northern Paraná, Brazil (Research, Society and Development, 2020)
Soil engineers play a predominant role in the formation and maintenance of soil structure, their activities affect the physical, chemical and biological processes of the soil ecosystem. The aim of this study was to perform a survey of the edaphic macrofauna community in a sugarcane cultivation on organic system. Soil samplings were made in the summer and winter in years of 2014 and 2015, using monolith separating soil in three layers. Soil samples were manually screened and the organisms identified. The values ​​of population abundance being submitted to Fisher LSD (p < 0.05) and ACP (Principal Component Analysis) were performed also. 5,760 ind m-² were found, concentrated in the upper layer of the soil (0-10 cm) and in the summer season. Predominated Formicidae, Chilopoda, Isopoda, Oligochaeta groups and, in this last one, peregrine species Pontoscolex corethrurus, suggesting long-term anthropic disturbances in the managed sites.